How group discussions create strong attitudes and strong partisans. (19th April 2016) - Levendusky, Matthew S.; Druckman, James N.; McLain, Audrey
Group discussions matter in politics—they affect individuals' attitudes as well as their political participation. But how do discussions influence the strength of attitudes? This is a question that has received scant attention, despite its relevance to both empirical and normative theories of democracy. We argue that group discussion generates strong attitudes via psychological elaboration. For many, this is a positive outcome. But we also show that discussion has a downside. Specifically, homogenous group discussions—which are the norm—strengthen partisan identities, which can increase partisan bias and motivated reasoning. Using an original experiment, we find strong support for our predictions. Our results, then, underline a tension in the political effects of group discussion: while it produces normatively desirable strong attitudes, it also creates more entrenched and potentially biased partisans.